Isolasi Jamur Endofit Pada Tanaman Anggur Bali (Vitis vinifera L. var. Alphonso Lavalle ) serta Efektivitasnya untuk Menekan Pertumbuhan Penyakit Busuk Kapang Kelabu pada Buah Anggur Bali - DEWI, NI LUH PUTU NOVITA; SUDARMA, I MADE; PHABIOLA, TRISNA AGUNG (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.8, No.4, Oktober 2019, 2019)
Endophytic Fungi Isolation on Balinese Grape Plants (Vitis vinifera L. var. Alphonso Lavalle ) and its Effectivenese to Control Grey Mold Disease on Balinese Grape Gray mold rot is the disease caused by pathogen Botrytis cinerea. It is an important disease in grapes (Vitis vinifera L.) since it can reduce the quantity and quality of grapes. Nowadays people use synthetic fungicides to control the pathogen, but the cost of synthetic fungicides is expensive and continuous usage will give a negative impact to the environment therefore endophytic fungus is an alternative way that can be used to control the pathogen in grapes. The purpose of this study was to obtain endophytic fungi and obtain the best endophytic fungus to control gray mold rot pathogens. This study uses two methods which are in vitro endophytic fungal antagonist test and in vivo endophytic fungal antagonist test in the laboratory. The results showed that there were 10 endophytic fungi. The results of in vitro and in vivo tests showed that the best endophytic fungus was Miselia sterilia A as confirmed by the percentage of inhibition of Miselia sterilia A in the in vitro test of 82.14% and the smallest percentage of pathogen attack in the in vivo test of 6%.